Modulation of Binding of DNA to the C-Terminal Domain of p53 by Acetylation - Friedler, Assaf; Veprintsev, Dmitry B.; Freund, Stefan M.V.; von Glos, Karoly I.; Fersht, Alan R. (Structure (London), 2005)
The binding of nonspecific DNA to the C-terminal negative regulatory domain (CTD) of p53 modulates its activity. The CTD is a natively unfolded region, which is subject to acetylation and phosphorylation at several residues as part of control. To measure the effect of covalent modification on binding to DNA, we synthesized a series of fluorescein-labeled CTD peptides with single and multiple acetylations at lysine residues that we had identified by NMR as making contact with DNA, and developed an analytical ultracentrifugation method to study their binding to DNA. Binding depended on ionic strength, indicating an electrostatic contribution. Monoacetylation weakened DNA binding at physiological ionic strength 2- to 3-fold, diacetylations resulted in further 2- to 3-fold decrease in the affinity, and tri- and tetraacetylations rendered DNA binding undetectable. Phosphorylation at S392 did not affect DNA binding. NMR spectroscopy showed binding to DNA did not induce significant structure into CTD, apart possibly from local helix formation.